PEMANFAATAN GOOGLE MAPS API DALAM PEMETAAN DESA WISATA DI INDONESIA BERBASIS WEBSITE - Lailyn Puad (JURNAL AKADEMIKA)
Information about existing tourist villages in Indonesia as well as location information is needed especially by potential travelers. This information is still very limited due to the absence of media that is able to bridge them. The authors designed a system that can be used as a liaison between village tourist managers with tourists. Using more interactive interactives and more accurate location search using Google Maps API is expected to have a significant impact on the widespread reach of the tourist villages so as to increase the incomes of nearby communities.